High-Performance Liquid Chromatography Assessment of Propofol Stability in Pharmaceuticals - Chikhale, Hemant U. (Asian Journal of Pharmaceutics (AJP), 2024)
Purpose: The objective of the current research was to provide a convenient, reliable, selective, and stabilityindicating high-performance liquid chromatographic (HPLC) approach for the assessment of propofol in pharmaceutical dosage forms. Materials and Methods: A forced degradation study was executed on propofol. The separation was performed on Thermo Scientific, ODS-2 (250 mm × 4.6 mm, 5 μm) column using acetonitrile: water (70:30 v/v) as mobile phase at a flow rate of 1 mL/min. The injection volume and wavelength of the detection were 20 μL and 272 nm, respectively. Results: Forced degradation study shows sufficient degradation in alkaline conditions. Whereas, in oxidizing and acidic conditions, less degradation was observed. No degradation was observed in thermal and photolytic conditions. A retention time was observed at 6.633 min. The calibration curve for propofol was found to be linear (R2 = 0.999) in the concentration from 5 to 30 μg/mL with a limit of detection and limit of quantification of 0.29 μg/mL and 0.89 μg/mL, respectively. The percent relative standard deviation value for all the analytical validation parameters such as specificity, linearity, and precision was found to be <2%. The recovery was found in the range of 98.01–04.72%. Conclusion: The method developed using reversed-phase HPLC was found suitable for the determination of propofol in pharmaceutical formulation.